(untitled) (Academia Journal of Medicine, 2020)
Background: The pathophysiology of diabetic nephropathy is complex and still not fully elucidated. Observational studies suggest a relationship of UA level with incident CKD, but studies evaluating the relationship with decline in kidney function in established CKD are conflictingSeveral prospective studies have suggested that hyperuricemia is associated with an increased risk of incident cardiovascular events and death in both nondiabetic and type 2 diabetic individuals Hyperuricemia also is largely prevalent in patients with chronic kidney disease(CKD). Subjects and Methods: The patients were randomly divided into two groups according group chosen by time of enrollment. By using simple random method, 64 study subjects will be taken, and the study subject is divided into 2 groups. A detailed history, anthropometry, vital signs, clinical examination and laboratory parameters were recorded for both the study group. Results: The Study reveals that, there was no statistical significant difference of mean serum uric acid among smokers and non-smokers in non-diabetes patients with CKD (P>0.05).Study reveals that, there was no statistical significant difference of mean serum uric acid among alcoholic and non-alcoholic cases in non-diabetes patients with CKD (P>0.05). Conclusion: non-diabetic patients with CKD cases (P<0.05). There was an increasing trend in the mean serum creatinine concentration with a corresponding decreasing trend in eGFR across increasing UA categories There is significantly sloping down of GFR with increase of SUA level as model.